STUDI PERILAKU KAWIN KUDA LAUT (Hippocampus kuda) DI BALAI BUDIDAYA LAUT LAMPUNG [Study on Mating Behaviour of Sea Horse {Hippocampus kuda) at Lampung Mariculture Center] - Tedjo Sukmono (Jurnal Iktiologi Indonesia, 2004)
The study aims to observe mating behavior and copulation type of seahorse (Hippocampus kuda). Treatment is ratio between female and male. The treatments consist of three sex ratio levels, there were A (1:2), B (1:3), C (1:4), and one control (1:1). Each treatment was replicated six times. The research was done during 90 days. The result showed that a female seahorse able to mate with more than one male in the one spawning season and the copulation type is polyandry.